Hepatitis E Virus Seroprevalence and Correlates of Anti-HEV IgG Antibodies in the Rakai District, Uganda. (23rd November 2017) - Boon, Denali; Redd, Andrew D; Laeyendecker, Oliver; Engle, Ronald E; Nguyen, Hanh; Ocama, Ponsiano; Boaz, Iga; Ndyanabo, Anthony; Kiggundu, Valerian; Reynolds, Steven J; Gray, Ronald H; Wawer, Maria J; et al.
Abstract : Hepatitis E virus seroprevalence among 500 HIV-infected adults and 500 controls in Rakai, Uganda was 47%, and did not differ by HIV status. Male sex and chronic hepatitis B virus infection were associated with seroprevalence. One active infection was detected. Abstract: A cross-sectional study was conducted of 500 human immunodeficiency virus (HIV)-infected adults frequency matched on age, sex, and community to 500 HIV-uninfected individuals in the Rakai District, Uganda to evaluate seroprevalence of anti-hepatitis E virus (HEV) IgG antibodies. HEV seroprevalence was 47%, and 1 HIV-infected individual was actively infected with a genotype 3 virus. Using modified Poisson regression, male sex (prevalence ratios [PR] = 1.247; 95% confidence interval [CI], 1.071–1.450) and chronic hepatitis B virus infection (PR = 1.377; 95% CI, 1.090–1.738) were associated with HEV seroprevalence. HIV infection status (PR = 0.973; 95% CI, 0.852–1.111) was not associated with HEV seroprevalence. These data suggest there is a large burden of prior exposure to HEV in rural Uganda.